Is intraoperative frozen section analysis of the proximal bile ducts in hilar cholangiocarcinoma of limited value?. (29th September 2016) - Ma, Wen‐Jie; Shrestha, Anuj; Li, Fu‐Yu
Abstract: Mantel et al. showed that the use of intraoperative frozen section analysis of the proximal bile ducts has a limited contribution in obtaining secondary R0 resections and final resection status had no impact on recurrence rate in hilar cholangiocarcinoma. However, the accuracy, sensitivity, and specificity of intraoperative frozen section analysis were determined by the specific pathologic features of the tumor and the different experienced pathologists in different pathology laboratories. It has been demonstrated that tumor‐free resection margin (R0) is the most prognostic factor for survival, as well as the only factor that can be modified by the surgeons. Ribero et al. reported an improvement in prognosis was found in the secondary R0 group. As the conclusion given by Mantel et al. and Shingu et al., which is contrary to Ribero et al. Before the real role of intraoperative frozen section in the analysis of the margin of proximal bile ducts in treating hilar cholangiocarcinoma is concluded, further studies are still needed. Abstract : As intra‐operative frozen section analysis of bile duct margins is the most used method to guide the surgical resection of hilar cholangiocarcinoma. Before the real role of intraoperative frozen section in the analysis of the margin of proximal bile ducts in treating hilar cholangiocarcinoma is concluded, further studies are still needed.